Personajes - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1987)
SPANISH: La fotografía muestra a Antonio Donadio junto a lideres Indigenas, en el conversatorio de Comunidades Indigenas
ENGLISH: The photograph shows Antonio Donadio together with indigenous leaders at the Indigenous Communities' conference.

SPANISH: La fotografía muestra a Antonio Donadio junto a lideres Indigenas, en el conversatorio de Comunidades Indigenas
ENGLISH: The photograph shows Antonio Donadio together with indigenous leaders at the Indigenous Communities' conference.
Characters
Keywords: S/N